2014
DOI: 10.1186/1471-230x-14-36
|View full text |Cite
|
Sign up to set email alerts
|

Screening for celiac disease in 1st degree relatives: a 10-year follow-up study

Abstract: BackgroundAlthough it is known that first degree relatives of celiac patients have an increased risk for celiac disease few studies are available on its incidence. We investigated the incidence of serologic conversion and of new cases of celiac disease among first degree relatives with negative results at a first screening.MethodsFrom a total of 634 first degree relatives of 186 biopsy-proven celiac disease patients diagnosed between October 2000 and October 2010, 450 subjects agreed to participate in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…Forty-eight studies were included in this part of analysis as they reported serological prevalence among FDRs with one index case of CD ( 9,(11)(12)(13)(14)(30)(31)(32)(33)(34)(35)(36)39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(52)(53)(54)(55)(56)(57)(58)(59)(60)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Overall, of 14,225 FDRs screened using AEA and/or anti-tTG Ab, 1,016 FDRs were seropositive ( 9,(11)…”
Section: Pooled Seroprevalence Of CD In Fdrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight studies were included in this part of analysis as they reported serological prevalence among FDRs with one index case of CD ( 9,(11)(12)(13)(14)(30)(31)(32)(33)(34)(35)(36)39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(52)(53)(54)(55)(56)(57)(58)(59)(60)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Overall, of 14,225 FDRs screened using AEA and/or anti-tTG Ab, 1,016 FDRs were seropositive ( 9,(11)…”
Section: Pooled Seroprevalence Of CD In Fdrsmentioning
confidence: 99%
“…In studies by Kurppa et al ( 37 ) and Aschler et al ( 51 ), the number of seropositive patients biopsied was not reported and combining data from these 2 studies, 107 individuals of 2,507 FDRs screened also had positive serology and histology compatible with CD. From these 39 studies, 602 FDRs were diagnosed with CD based on positive serology (either anti-tTG Ab and/or AEA) and villous abnormalities ≥modifi ed Marsh grade 2 ( Table 2 ) ( 9,(11)(12)(13)(14)(30)(31)(32)(33)(34)(35)(36)(37)39,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(74)(75)(76)(77)(78).…”
Section: Pooled Prevalence Of CD In the Fdrsmentioning
confidence: 99%
“…Finally, family histories of RA [36,37] and CD [38,39] and their corre- The presence of anti-citrullinated protein antibody is a standard test 233 for rheumatoid arthritis, and it is associated with more severe disease. tion in animal studies [80][81][82][83][84].…”
mentioning
confidence: 99%
“…May be, this selection of patients in the family already had (albeit minor) complaints. A large multi-center study from the USA showed a rate of only 5% in both first and second degree relatives [17,18]. We suggest that 4e5% reflects appropriately the true rate in daily practice.…”
Section: Screening In Celiac Familiesmentioning
confidence: 66%